Production Technology and Functionality of Bioactive Peptides - Wen, Qingmei; Zhang, Lei; Zhao, Feng; Chen, Yilu; Su, Yi; Zhang, Xiaochun; Chen, Pu; Zheng, Tao (Current Pharmaceutical Design, 2023)
Bioactive peptides are specific protein fragments that prove health-promoting potential for humans. The bioactivities include antimicrobial, antioxidant, anticancer, immunomodulatory activities, etc. Hence, bioactive peptides' production technology and processes have attracted excessive attention, especially concerning peptides' synthesis, separation, identification, and functionality. This review summarizes the relevant investigations from the above four aspects. Among the production technology of bioactive peptides, biosynthesis, chemosynthesis, technology for separation and purification, and the interactions responsible for peptide-based nanostructures are emphasized. Here, the biosynthesis of peptides includes enzymatic hydrolysis, microbial fermentation, and recombinant DNA technology, and chemosynthesis consists of solution-phase peptide synthesis and solid-phase peptide synthesis (SPPS). The commonly used enzymes in enzymatic hydrolysis are investigated, including pepsin, trypsin, and alcalase. The commonly used microorganisms, typical processes, protein sources, and advantages of microbial fermentation are analyzed. Membrane separation (including ultrafiltration and nanofiltration), chromatography technology (including ion-exchange chromatography, gel filtration chromatography, affinity chromatography, and reverse-phase high-performance liquid chromatography (RP-HPLC)), and electrophoresis technology are detailed for the purification technology. Mass spectrometry (MS), its combination with the high-performance separation method, and nuclear magnetic resonance (NMR) are elucidated for the identification technology. The non-covalent interactions responsible for peptide-based nanostructures involve electrostatic force, hydrogen bonds, π-π stacking, hydrophobic interaction, and van der Waals force. Afterward, we detail the peptides' antihypertensive, antithrombotic, anticancer, antimicrobial, antioxidant, and immunomodulatory activities. The activity analysis mainly involves peptides' sources, structural features, mechanisms of action, and influencing factors. Based on the production and functionality elucidation, potential challenges for peptide application in biomedicine are given. The challenge is analyzed from the aspects of purification and identification technologies and influencing factors of peptides' bioactivities. Our work will elaborate on advances in the production technology of peptides and their bioactivities, which could promote and expand their industrial applications.
Keywords: biosynthesis